Examining the production amount of milk and dairy products using network analysis in Turkey - AKIN, Ahmet Cumhur; ARIKAN, Mehmet Saltuk; POLAT, Murat; MAT, Burak; ÇEVRİMLİ, Mustafa Bahadır; DEMİRSÖZ, Mert; TEKİNDAL, Mustafa Agah (FapUNIFESP (SciELO), 2022)
Abstract Among the sub-branches of the livestock industry in Turkey, milk and dairy product sector is one of the most active production areas. It is essential to examine the supply structure of the milk and dairy product sector and reveal the relations between the production amounts of the products to understand the overall structure of the sector. We determined the pattern network structures based on the amount of raw cow milk entering the industry and the production amounts of six products between 2010/01 and 2020/09. In addition, we studied the product-based development of the sector. The findings obtained from the network analysis of the production amounts of milk and dairy products indicated a relationship between the products and their interactions with each other. The amount of raw milk entering the production process was located in the center and displayed a positive relationship with all products it interacted with. The amount of raw cow milk entering the production process and the amount of cow cheese produced affected other products included in the network. In addition, among the products produced, the production amounts of ayran and yogurt exhibited the highest correlation coefficient with a moderate positive correlation value (0.609). The resulting social network graph provides important clues about the general production understanding of Turkey’s dairy sector and consumer preferences in the market.
Keywords: dairy industry; Turkey; dairy products; raw milk; network analysis; 2. Zero hunger